2014
DOI: 10.1016/j.clp.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Prevention of Intraventricular Hemorrhage

Abstract: SYNOPSIS Intraventricular hemorrhage (IVH) is a major neurological complication of prematurity. Pathogenesis of intraventricular hemorrhage is attributed to intrinsic fragility of germinal matrix vasculature and to the fluctuation in the cerebral blood flow. Germinal matrix exhibits rapid angiogenesis orchestrating formation of immature vessels. The angiogenic vessels lack pericytes, display immature basal lamina low in fibronectin, and have astrocyte end-feet coverage deficient in glial fibrillary acidic prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
232
1
30

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(269 citation statements)
references
References 125 publications
(127 reference statements)
6
232
1
30
Order By: Relevance
“…Contrary to other studies, which showed a decrease in IVH with antenatal steroids, our study did not show a significant difference between the use of antenatal steroids in the case and control groups. [3] This may be due to the fact that the administration of antenatal steroids in our setting was lower than in other settings. Only 43% of mothers of VLBW infants had received steroids compared with 83.5% of those in the VON during the same period, which may have been due to late presentation of unbooked mothers.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Contrary to other studies, which showed a decrease in IVH with antenatal steroids, our study did not show a significant difference between the use of antenatal steroids in the case and control groups. [3] This may be due to the fact that the administration of antenatal steroids in our setting was lower than in other settings. Only 43% of mothers of VLBW infants had received steroids compared with 83.5% of those in the VON during the same period, which may have been due to late presentation of unbooked mothers.…”
Section: Discussionmentioning
confidence: 57%
“…Mechanical ventilation and PDA also had an increased association with IVH and this can be explained by fluctuations in cerebral blood flow. [3] The prevalence of IVH in inborn patients was less compared with those who were outborn, and there are many factors that could explain the higher risk, including delay in transfer, inadequate monitoring, and lack of appropriate management at referring centres. Contrary to other studies, which showed a decrease in IVH with antenatal steroids, our study did not show a significant difference between the use of antenatal steroids in the case and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 El cráneo fácilmente deformable, sobre todo en el bebé prematuro, puede elevar la presión venosa durante el parto vaginal, llevando a la idea que el parto por cesárea podría reducir estas complicaciones. No obstante, la evidencia parece indicar que la evitación del parto vaginal no confiere ninguna ventaja para el feto prematuro con pre-sentación cefálica, ni jugar un rol significativo en el deterioro del neurodesarrollo en neonatos de bajo y muy bajo peso al nacer.…”
Section: Partounclassified
“…2 Cerca de 50-75% dos prematuros com HPIV desenvolveram paralisia cerebral, retardo mental e/ desenvolveram distúrbios psiquiátricos. 3 e das HPIV, esta quase exclusiva em pré-termos, contribuem prematuros. Essas hemorragias, tanto intraparenquimatosas de vários fatores, entre eles: maior vulnerabilidade dos vasos o surgimento dessa patologia em crianças a termo, cujos nesses pacientes.…”
unclassified